[Complementarity and Interrelations of Shifts in Demand]: A Comment - Hicks, J. R. (Review of Economic Studies, 1940)
Journal Article A Comment Get access J. R. Hicks J. R. Hicks Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 8, Issue 1, October 1940, Pages 64–65, https://doi.org/10.2307/2967420 Published: 01 October 1940